2012
DOI: 10.1590/s0004-27302012000700001
|View full text |Cite
|
Sign up to set email alerts
|

Insulin analogues in the treatment of diabetes in pregnancy

Abstract: SUMMARYPregnancy affects both maternal and fetal metabolism, and even in non-diabetic women, it exerts a diabetogenic effect. Among pregnant women, 2% to 14% develop gestational diabetes. Pregnancy can also occur in women with preexisting diabetes, which may predispose the fetus to many alterations in organogenesis, restrict growth, and the mother, to some diabetes-related complications, such as retinopathy and nephropathy, or to acceleration of the course of these complications, if they are already present. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…In general, insulin analogs may reduce the risk of hypoglycemia and promote a more physiological glycemic profile than regular human insulin in pregnant women with T1D, T2D, or GDM [ 34 ]. However, there are a number of potential concerns associated with the use of these agents during pregnancy.…”
Section: Insulins Available For Use In Pregnancymentioning
confidence: 99%
See 3 more Smart Citations
“…In general, insulin analogs may reduce the risk of hypoglycemia and promote a more physiological glycemic profile than regular human insulin in pregnant women with T1D, T2D, or GDM [ 34 ]. However, there are a number of potential concerns associated with the use of these agents during pregnancy.…”
Section: Insulins Available For Use In Pregnancymentioning
confidence: 99%
“…Although data from randomized controlled trials (RCTs) are limited, experience with insulin lispro and insulin aspart has generally indicated that these RAIAs produce similar outcomes to regular human insulin in pregnant women with T1D, T2D, or GDM [ 34 , 39 42 ]. These latter findings have led to the conclusion that there is no evidence of an adverse effect of these insulins on pregnancy or on the health of the fetus/newborn [ 34 , 36 , 37 , 41 , 43 , 44 ].…”
Section: Insulins Available For Use In Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…This pathology accounts for ~5% of pregnant women worldwide and it is associated with high risk of fetal perinatal alterations (e.g., macrosomia, insulin resistance) and higher incidence of diseases in the adulthood (e.g., GD, obesity, dyslipidemia, hypertension, metabolic syndrome) (Poston, 2010; Negrato et al, 2012). GD is associated with reduced maternal circulating T 4 levels in the first trimester of pregnancy.…”
Section: Maternal T4 Level and Gdmentioning
confidence: 99%